2018
DOI: 10.1007/s11418-018-1251-5
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of β-carboline and canthinone alkaloids as anti-inflammatory agents but with different inhibitory profile on the expression of iNOS and COX-2 in lipopolysaccharide-activated RAW 264.7 macrophages

Abstract: A compound library, which consists of 75 natural β-carboline-type or canthinone-type alkaloids from Simaroubaceae plants and their chemical synthetic analogues, was screened for the anti-inflammatory activity by inhibition of the overproduction of inflammatory mediator nitric oxide (NO) in lipopolysaccharide (LPS)-activated RAW 264.7 macrophage cells. Six compounds, namely, benzalharman ( 23 ), kumujian ( 27 ), 1-ethyl-1,2,3,4-tetrahydro-β-carboline-3-carboxylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“… 69 β-Carboline alkaloids may occur in many plant-derived foods, thermally processed protein-rich foods, and beverages, 70 and were demonstrated to exhibit anti-inflammatory activity via potent inhibition of nitric oxide (NO), TNFα, and interleukin-6 (IL6). 71 , 72 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 69 β-Carboline alkaloids may occur in many plant-derived foods, thermally processed protein-rich foods, and beverages, 70 and were demonstrated to exhibit anti-inflammatory activity via potent inhibition of nitric oxide (NO), TNFα, and interleukin-6 (IL6). 71 , 72 …”
Section: Discussionmentioning
confidence: 99%
“…69 β-Carboline alkaloids may occur in many plant-derived foods, thermally processed protein-rich foods, and beverages, 70 and were demonstrated to exhibit anti-inflammatory activity via potent inhibition of nitric oxide (NO), TNFα, and interleukin-6 (IL6). 71,72 1,3-DCP, an unannotated compound (C8H8F3N3O4S2), and AFMK were the three main compounds showing high correlations with the WBC count. The first two compounds were positively correlated with WBCs, while AFMK was inversely correlated with WBCs.…”
Section: Negative-ion Modementioning
confidence: 95%
“…First, the coupling of 177b with various amino acid esters was performed, then a formyl moiety was formed via acidic treatment of the acetal, followed by the same three steps described previously to form the other four metatacarbolines (32)(33)(34)(35). The first total synthesis of 6-hydroxymetatacarboline D (36) has been developed in 12 steps by Meng et al via CuBr2-catalyzed mild oxidation method by the dehydrogenation of the DHβC's C-ring (Scheme 17) [129]. The synthesis starts from 5-hydroxytryptophan (179), which was converted into Boc-and benzyl-protected compound 182 by applying protecting group chemistry.…”
Section: Co Mementioning
confidence: 99%
“…Noctiluca milaris [10] Strychnos johnsonii [11] Lycoris longituba [12] Selaginella delicatula [13] Trichosanthes kirilowii Maxim [14] Rauwolfia caffra [15] Didemnum sp [16] MAO Cnemidocarpa stolonifera [20] apoptosis in PC3 human prostate cancer cell line [20] 8: Eudistoma olivaceum [21] 9: Eudistoma olivaceum [22] 10: Lissoclinum fragile [23] 11: Eudistoma olivaceum [24] 12: analogues of natural products 13: soybean [28] Flindersia laevicarpa [29] 14: analogues of natural products 15: Flindersia Caevicarpa [29] 16: Picrasma quassioides [30] 13: anti-neuroin-flammatory activities [28] 14: n.a. 15: vasorelaxant effect [31] binding affinity to imidazoline I2B receptors [32] 16: cytotoxic activity [33] AMP phosphodiesterase inhibitor [34] anti-inflammatory agent [35,36] trigonostemine [37] 17, 18, 19: Trigonostemone filipes [38] 20: Malassezia furfur [39] Paracoccus marine bacteria [40] Dichotomomyces cejpii [41] 21: Hyrtio erectus [42] Alocasia macrorrhiza [43] 17, 18, 19: cytotoxic activity [44] 20: antiproliferative activity [45] anticancer activity [46,47] 21: antiproliferative activity [48,49] antimalarial activity [46] antiphospholipase A2 [50] and antioxidant activity …”
Section: Introductionmentioning
confidence: 99%
“…Further investigations on these hits for their inhibitory effect on PGE 2 production and on expression of iNOS and COX‐2 proteins revealed that β‐carboline‐type alkaloids weakly inhibit iNOS expression and are inactive against COX‐2. In a sharp contrast, cathinone‐type alkaloids ( 87 and 88 ) inhibited both the production of NO and release of PGE 2 with good potency . Evaluation of some alkaloids, phenolic compounds, and fatty acid methyl esters, isolated from fruiting bodies of mushroom Calvatia nipponica (Agaricaceae), for NO inhibitory activity in LPS‐induced RAW‐264.7 macrophages has led to identification of fatty acid methyl ester 89 as a NO inhibitor (IC 50 27 µM) …”
Section: Natural Inos Inhibitorsmentioning
confidence: 99%